Seminar of Johor industrial aims and prospects towards the year 2000, 19th-20th Oct 1991 : information package - Seminar of Johor Industrial Aims and Prospects Towards the Year 2000 (1991 : UTM); Universiti Teknologi Malaysia. Fakulti Pengurusan dan Pembangunan Sumber Manusia. Persatuan Pengurusan Teknologi (STRATEGI)
36